2022
DOI: 10.34133/2022/9780879
|View full text |Cite
|
Sign up to set email alerts
|

Mussel-Inspired and Bioclickable Peptide Engineered Surface to Combat Thrombosis and Infection

Abstract: Thrombosis and infections are the two major complications associated with extracorporeal circuits and indwelling medical devices, leading to significant mortality in clinic. To address this issue, here, we report a biomimetic surface engineering strategy by the integration of mussel-inspired adhesive peptide, with bio-orthogonal click chemistry, to tailor the surface functionalities of tubing and catheters. Inspired by mussel adhesive foot protein, a bioclickable peptide mimic (DOPA)4-azide-based structure is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 63 publications
(52 reference statements)
0
19
0
Order By: Relevance
“…With this in mind, we turned our attention to biomimetic strategies. Enlightened by the anchoring property of marine mussels on various surfaces, DOPA (3,4-dihydroxy-L-phenylalanine), which is abundant in Mytilus edulis foot proteins (Mefps), has attracted extensive attention [19][20][21]. A previous study showed that DOPA exhibits strong adhesion on the surface of wet metals through interactions between covalent cross-linking units, metal bidentate coordination, and hydrogen bonding regulated by catechol groups [22].…”
Section: Introductionmentioning
confidence: 99%
“…With this in mind, we turned our attention to biomimetic strategies. Enlightened by the anchoring property of marine mussels on various surfaces, DOPA (3,4-dihydroxy-L-phenylalanine), which is abundant in Mytilus edulis foot proteins (Mefps), has attracted extensive attention [19][20][21]. A previous study showed that DOPA exhibits strong adhesion on the surface of wet metals through interactions between covalent cross-linking units, metal bidentate coordination, and hydrogen bonding regulated by catechol groups [22].…”
Section: Introductionmentioning
confidence: 99%
“…Developing antibacterial surfaces for implantable medical devices also is currently a hot direction among the Chinese communities focusing on biomaterials science and engineering. Typical designs published in the first half of 2022 include copper-bearing titanium [ 12 ], surface charge and wettability control in lysozyme [ 13 ], light-activatable carbon monoxide gas generation by triiron dodecacarbonyl loaded polydopamine [ 14 ], clickable peptide engineered surface [ 15 ], calcium-doped titanium targeting blood protein adsorption [ 16 ], puncture and ROS (reactive oxygen species) release by nanorod zinc oxide patterns [ 17 ], light-stimulated ROS generation by rare-earth elements-doped titanium dioxide coating [ 18 ], on-demand antibiotics release by responsive polymers [ 19 , 20 ], and bacteriophage-modified alginate hydrogels [ 21 ]. This trend demonstrates that the academic community has already realized the urgency of solving the DAI problem, whereas only a limited number of these innovations have entered clinical applications or clinical studies around the world.…”
Section: Introductionmentioning
confidence: 99%
“…The Layer-by-Layer (LbL) assembly technique, as a widely used effective and facile coating strategy, can integrate diverse functional components on implant surfaces via molecular interactions. However, the combination of organic and inorganic ingredients via the LbL method may pose a challenge since it requires various types of molecular interactions for bonding between each layer, such as hydrogen bonds, chelation, hydrophobic, or electrostatic interactions. Inspired by mussels, which can attach to almost all kinds of inorganic and organic surfaces, polyphenols have great potential to be applied to preparing organic–inorganic coatings via the LbL method due to their universal adhesive capacity. , …”
Section: Introductionmentioning
confidence: 99%
“…30−32 Inspired by mussels, which can attach to almost all kinds of inorganic and organic surfaces, polyphenols have great potential to be applied to preparing organic−inorganic coatings via the LbL method due to their universal adhesive capacity. 33,34 In view of these observations, a polyphenol-assisted LbL method was designed to form a multifunctional organic− inorganic implant coating. Tannic acid (TA), a natural polyphenol with abundant catechol groups, was introduced as a polyphenol bridge considering it has been widely used in the biomedicine field with good biosafety, accessibility, and affordability.…”
Section: Introductionmentioning
confidence: 99%